Tribute to Stephen Hawking:: six life lessons that scientists should remember (Sustainability in Debate, 2018)
“We are just an advanced breed of monkeys on a minor planet of a very average star. But we canunderstand the Universe. That makes us something very special.”On March 14, 2018, after 76 years of living a purpose driven life, Stephen Hawking left Earth. He wantedto gain a total comprehension of the Universe by questioning his own existence and special characteristics.One of his recommendations was that one should always look up at the stars, not down at his own feet.“Try to make sense of what you see and wonder about what makes the universe exist”, he said. “Be curious.”